Presurgical evaluation algorithm of epilepsy and its practical significance - Buniakin, Viacheslav M. (Ukrainian Neurosurgical Journal, 2023)
Objective: Evaluation of the efficacy of surgical treatment for different forms of epilepsy using individualized complex presurgical diagnostic algorithms. Materials and Methods: The study included 104 patients with localized unifocal forms of epilepsy and 48 patients with multifocal epilepsy. Among them, 68 (44.7%) were children and 84 (55.3%) were adults. Patients' age ranged from 2 to 63 years. All patients had frequent epileptic seizures and unsatisfactory results of medical treatment. Recurrent status epilepticus or serial seizures in the anamnesis were presented in 74 cases (48.7%). Medication for all patients before surgery treatment included from 1 to 8 antiepileptic drugs. Postsurgical follow-up lasted from 4 months to 16 years. Main examinations included: complete medical history, types of epileptic seizures, EEG or video-EEG, brain MRI. Additional examinations included: MRI - tractography and functional MRI, single-photon emission computed tomography (SPECT), positron emission tomography, subtraction ictal SPECT co-registered to MRI, and intraoperative corticography. Results: The use of presurgical evaluation algorithm made it possible to localize epileptogenic foci (EF) in all patients. The method of surgical intervention was chosen only of the received preoperative data. Seizures free (Engel Ia) was achieved in 67 (44.1%) patients. Single focal or nocturnal seizures (Engel Ib-c) were reported in 37 (24.3%) patients. Significant regression of the number of epileptic seizures (Engel II) was achieved in 28 (18.4%) cases, and moderate regression (Engel III) - in 12 (23.1%) patients. Absence of positive dynamics after surgery (Engel IV) occurred in 7 (4.6%) patients. Surgical complications occurred in 13 (8.6%) patients. Conclusions: Presurgical evaluation algorithm helped localize unifocal and multifocal EF, which allows choosing a surgical technique, accurately planning the stategy of intervention and carrying it out safely. In cases of surgical impact on EF, it is possible to achieve complete seizure control.